Hypofractionated proton therapy for non-small cell lung cancer: Ready for prime time? A systematic review and meta-analysis. (November 2022) - Volpe, Stefania; Piperno, Gaia; Colombo, Francesca; Biffi, Annalisa; Comi, Stefania; Mastroleo, Federico; Maria Camarda, Anna; Casbarra, Alessia; Cattani, Federica; Corrao, Giulia; de Marinis, Filippo; Spaggiari, Lorenzo; et al.
Highlights: Hypofractionated proton beam radiotherapy for early-stage non-small cell lung cancer is gaining attention. The optimal treatment schedule in terms of oncological outcomes and toxicities has not been defined. The delivery of BED ≥ 105.6 Gy(RBE) is associated with improved survival, disease-free survival and local control. Dose escalation may be associated with a slight increase in late toxicities, albeit medically manageable and non life-threatening. Optimized patients' selection and the use of advance uncertainty management techniques are mandatory. Abstract: Background: Hypofractionated proton beam radiotherapy (PBT) is gaining attention in early-stage non-small cell lung cancer (ES-NSCLC). However, there is a large unmet need to define indications, prescription doses and potential adverse events of protons in this clinical scenario. Hence, the present work aims to provide a critical literature revision, and to investigate associations between fractionation schedules/ biological effective doses (BEDs), oncological outcomes and toxicities. Materials and methods: This systematic review and meta-analysis complied with the PRISMA recommendations. Inclusion criteria were: 1) curative-intent hypofractionated PBT for ES-NSCLC (≥3 Gy(RBE)/fraction), 2) report of the clinical outcomes of interest, 3) availability of full-text written in English. The bibliographic search was performed on the NCBI Pubmed, Embase and Scopus in September 2021; no other limitations were applied. The BED was calculated for each included study (α/β = 10 Gy); the median BED for all studies was used as a threshold for stratifying selected evidence into "high" and "low"-dose subgroups. Heterogeneity was tested using chi-square statistics; inconsistency was measured with the I 2 index. Pooled estimate was obtained by fitting both the fixed-effect and the DerSimonian and Laird random-effect model. Results: Eight studies and 401 patients were available for the meta-analysis; median follow-up was 32.8 months. The median delivered BED was 105.6 Gy(RBE). A BED ≥ 105.6 Gy(RBE) consistently provided superior OS, CSS, DFS and LC rates (i.e.: 4-year OS: 0.56 [0.34–0.76] for BED < 105.6 Gy(RBE) and 0.78 [0.64–0.88] for BED ≥ 105.6 Gy(RBE)). The meta-analysis of proportions showed a comparable probability of developing acute grade ≥ 2 toxicity between the two groups, while the probability of any late grade ≥ 2 event was almost three-times greater for BED ≥ 105.6 Gy(RBE), with rib fractures being more common in the high dose group. Conclusion: Hypofractionated PBT is a safe and effective treatment option for ES-NSCLC; the delivery of BED ≥ 105.6 Gy(RBE) with advanced techniques for uncertainty management has been associated with improved oncological outcomes across all considered time points.